LATEST PERMIAN AND TRIASSIC CARBONATES OF RUSSIA: NEW PALAEONTOLOGICAL FINDINGS, STABLE ISOTOPES, CA-MG RATIO, AND CORRELATION - Zakharov Y.D.; Ukhaneva N.G.; Ignatyev A.V.; Afanasyeva T.B.; Buryi G.I.; Panasenko E.S.; Popov A.M.; Punina T.A.; Cherbadzhi A.K. (My University, 2000)
The seven recently discovered events, respectively occurring at (1) early Dorashamian, (2) middle Olenekian, (3) early Anisian, (4) latest Ladinian-?earliest Carnian, (5) late Carnian, (6) early Norian and (7) early Rhaetian intervals, are characterised by anomalously high value of δ 13C (2.5-6.9‰) and a more or less considerable decline in Ca-Mg ratio in organogenic carbonates of the Tethyan Realm The geochemical variations appear explaiable by high bioproductivity of marine basins during periods of transgressions and warm climate. The highest δ 13C values identified in Triassic limestones of the Malaya Laba (6.9‰) and Sakhrai (4.2‰) River basins in North Caucasus and Primorye region (4.9‰) fall at the middle Olenekian Tirolites-Amphistephanites Zone and its equivalents. Oxygen isotope analyses of well preserved brachiopod shells from the Nikitinskaya and Urushtenskaya Suites show that shallow-water temperatures in North Caucasus fluctuated during Early Dorashamian time about 24°C, which is in agreement with our previous data from the Dorashamian Paratirolites kittli Zone in Transcaucasia (around 22-24°C). Similar temperatures appear to have occured in the Tethys at least during the middle Olenekian time.
Keywords: Triassic; Permian; Mesozoic::Triassic; Paleozoic::Permian; Мезозой::Триасовая; Палеозой::Пермская